Retrotransposon-mediated disruption of a chitin synthase gene confers insect resistance to Bacillus thuringiensis Vip3Aa toxin - Liu, Zhenxing; Liao, Chongyu; Zou, Luming; Jin, Minghui; Shan, Yinxue; Quan, Yudong; Yao, Hui; Zhang, Lei; Wang, Peng; Liu, Zhuangzhuang; Wang, Na; Li, Anjing; et al. (PLoS biology, 2024)
The vegetative insecticidal protein Vip3Aa from Bacillus thuringiensis (Bt) has been produced by transgenic crops to counter pest resistance to the widely used crystalline (Cry) insecticidal proteins from Bt. To proactively manage pest resistance, there is an urgent need to better understand the genetic basis of resistance to Vip3Aa, which has been largely unknown. We discovered that retrotransposon-mediated alternative splicing of a midgut-specific chitin synthase gene was associated with 5,560-fold resistance to Vip3Aa in a laboratory-selected strain of the fall armyworm, a globally important crop pest. The same mutation in this gene was also detected in a field population. Knockout of this gene via CRISPR/Cas9 caused high levels of resistance to Vip3Aa in fall armyworm and 2 other lepidopteran pests. The insights provided by these results could help to advance monitoring and management of pest resistance to Vip3Aa.